P215 Non – caseating splenic granulomas as the first manifestation of very early onset inflammatory bowel disease (VEO-IBD). (6th June 2017) - Mardare, Roxana; Modi, Anita; Lindley, Keith; Ashworth, Meena; Rollins, Hazel; Ramkumar, Nisha
Abstract : Background: Splenic granulomas (SG), are rare and a challenge in terms of diagnosis and treatment. There is no reported incidence for SG and they usually appear in young adults. Our patient presented with SG, as an extra-intestinal manifestation of VEO-IBD, which is described in children with ages between 2 to 6 years. Case Report: We report the case of a 3 year old girl who developed multiple SG at the onset of Crohn's Disease (CD), making her, to our knowledge, the youngest patient reported to have this extra-intestinal manifestation of IBD. Our patient presented after a few months of recurrent episodes of fever, vomiting, abdominal pain, weight loss and mouth ulcers. No infectious aetiology was found and she had normal immunological workup, CXR and Echocardiogram. Ultrasound (USS) of the abdomen showed hypoechoic splenic lesions. Intravenous (IV) Ceftriaxone and Metronidazole were started. Splenic biopsy was performed, as despite an 8 week course of IV and oral antibiotics there was no resolution of her symptoms and USS findings. Splenic biopsy showed non-caseating granulomas. She had further tests: tuberculosis screening and faecal calprotectin (FC). Her FC was raised, hence she had upper and lower gastrointestinal tract endoscopies and video capsule endoscopy (VCE), which showed multiple ulcers throughout the small bowel, confirming a diagnosis of VEO-CD. She was started on Modulen and Azathioprine and her gut symptoms and SG resolved on the USS. After the initial improvement her gut symptoms returned and Infliximab was then added to her management. Results: Four months after commencing Infliximab, our patient experienced abdominal pain, mouth ulcers and anorexia. Her repeat FC was elevated. Repeat endoscopies and MRI reconfirmed the diagnosis of active CD in the stomach, small bowel and colon. Both Azathioprine and Infliximab doses were increased with improvement in symptoms. Her splenic lesions resolved after initial dietary treatment. She is being monitored with regular abdominal ultrasound. Conclusion: Our case is unique due to the age of the patient and the atypical features of VEO-IBD, the splenic manifestation preceding the gut disease. Her symptoms were comparable to those of patients with SG. Similar to our case, patients with VEO-IBD usually do not respond to first line treatment, therefore biologics are often used early on in this disorder. Further studies on VEO-IBD need to be undertaken to help us manage this unusual disease entity.